Unexpected Detection of Anti-SARS-CoV-2 Antibodies Before the Declaration of the COVID-19 Pandemic - Mahallawi, Waleed; Ibrahim, Nadir (Frontiers in Medicine, 2022)
Background: Limited information is currently available regarding the global incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections prior to the declaration of the coronavirus disease 2019 (COVID-19) pandemic, which may result in improper conclusions regarding the timing of viral transmission. Methods We investigated the presence of specific antibodies against the receptor-binding domain (RBD) of SARS-CoV-2 in archived serum samples that were collected from 478 healthy blood donors and patients in Madinah, Saudi Arabia, between October 2019 and January 2020. Enzyme-linked immunosorbent assay (ELISA) was performed to measure SARS-CoV-2 IgM and IgG antibodies. In addition, rheumatoid factor (RF) and urea dissociation tests were performed in all samples, which showed seropositivity for the SARS-CoV-2 IgM antibody. Additionally, Chemiluminescence immunoassays (CLIA) targeting the RBD of the SARS-CoV-2 spike (S) protein were performed to confirm the seropositivity of the samples. Results Overall, 20 (4.18%) serum samples were detected by ELISA to have SARS-CoV-2 IgG or IgM antibodies. Of these, 12 (2.51%) samples were positive for IgM antibody, and 8 (1.67%) were positive for IgG antibody. The 12 samples positive for SARS-CoV-2 IgM antibody were subjected to RF and urea dissociation tests, and all samples were RF-negative. The ELISA results were negative for 7 (58.33%) samples when subjected to urea dissociation prior to ELISA, whereas the other 5 (41.67%) samples remained positive. These 5 samples remained positive for the anti-S RBD IgG antibody in the CLIA. In addition, 3 of the 8 samples with IgG positivity according to the ELISA remained positive in the CLIA. After reviewing their data, we discovered that the 8 CLIA-confirmed positive samples were obtained from returned travellers who had visited China during the 4-week period immediately preceding blood donation. Conclusion In conclusion, we found evidence to support the early circulation of SARS-CoV-2 among persons who visited China a few months prior to the pandemic declaration. These results can be used to better define the spread of SARS-CoV-2 infections before the COVID-19 pandemic declaration. The detection of SARS-CoV-2 antibodies in individuals before the pandemic was declared in China could rewrite the pre-pandemic timeline.